LGBT psychology and mental health emerging research and advances - Ruth, Richard; Santacruz, Erik (Practical and applied psychology., 2017)
"This book presents emerging discoveries, trends, and research areas in LGBT psychology, both in science and therapy. It brings together concise, substantive reviews of what is new or on the horizon in science and in key areas of clinical practice, and provides information and insight to help psychologists, mental health clinicians, and counselors better serve the LGBT populations that, increasingly, are seeking their services"--Publisher's description.